RAILWAY TIMETABLE RESCHEDULING OF AUTOMATED PEOPLE MOVER USING MAX-PLUS ALGEBRA AND ROBUST MODEL PREDICTIVE CONTROL - Aditya Hidayat, Andri
Railway transportation is a mode of transportation that has great efficiency, reliability and capacity. The presence of Communication-Based Train Control (CBTC) yields a good impact in many ways such as more accurate train scheduling and train information easily obtained by passenger. The enthusiasm and satisfaction of the public towards this transportation have an impact on accumulation of passenger number at certain stations during rush hours. Increasing headway of train makes disturbances in the form of delays and other more prone to occur. If this delay is not immediately resolved by rescheduling, it can propagate to the next stations and interfere passenger satisfaction. Rescheduling is the main solution to reduce the impact of train departure delay.